The Auckland School of Music, Post-Modernism & Nervous Laughter - Linzey, Kate (Architectural History Aotearoa, 2009)
In 1984, the book-of-the-television-show The Elegant Shed was released by Otago University Press, and subsequently reviewed by Libby Farrelly in New Zealand Architect (1985) 2:39-40. Declaring the cover "wholly seductive ... glutinous sensuality," but its contents only "occasionally brilliant," Farrelly asks a lot of a not very big volume: to be "a definitive treatise on New Zealand's architecture." Though concluding that such a demand was "unsupporting" Farrelly's persistent fear is that David Mitchell and Gillian Chaplin lacked a "valiant idea." The review included the plan of Hill, Manning, Mitchell Architects' design for the Auckland School of Music. Citing Mitchell's comment in The Elegant Shed that "there was no logical connection between the side of a grand piano and the shape of a noise deflecting wall," Farrelly warns that such arbitrary aesthetics condemns architecture to mere "applique." Though "applique" is not, strictly speaking, collage, patching together is an apt description of the design process evident in the Music School plan. In their description of the design Hill, Manning, Mitchell Architects tauntingly declared that the project contains elements of "Baroque, Spanish Mission and Post-Modern" architecture (New Zealand Architect (1981) 5/6:1-3), and suggested that their transition from being "straight-line modernists" to "sensuous and baroque... [is] not unexpected in middle age." This paper will discuss Manning & Mitchell's design of the Auckland Music School in the context of their own writings and seminal international texts on the post-modern architecture, Learning From Las Vegas (1972) and Complexity and Contradiction (1966) by Robert Venturi et al. and Colin Rowe's Collage City (1978). I will argue that the hardest thing for architecture to bear/bare, especially New Zealand architecture, is a sense of humour.